PI3Kδ hyper-activation promotes development of B cells that exacerbate Streptococcus pneumoniae infection in an antibody-independent manner - Anne-Katrien Stark (Nature Portfolio, 2018)
Antibody mediated immune responses to Streptococcus pneumoniae are crucial for the immune response to infection. Here the authors show hyper-activation of PI3Kδ promotes development of a subset of B cells that exacerbate infection in an antibody-independent manner and can be reversed by therapeutic targeting in vivo.